Theoretical and experimental performance evaluation methods for DD-OFDM systems with optical amplification - Adolfo V. T. Cartaxo (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Several methods have been proposed to evaluate theoretically and experimentally the performance of optically amplified direct-detection orthogonal frequency division multiplexing systems. In this paper, we review those methods, and highlight their main advantages and disadvantages.